B → J / ψ K ( 1270 ) and B → J / ψ K ( 1400 ) Decays in QCD Factorization Approach - Mahboobeh Sayahi; Hossein Mehraban (Advances in High Energy Physics)
The hadronic B → J / ψ K ( 1270 ) and B → J / ψ K ( 1400 ) has been analyzed in “QCD factorization” approach and generalized factorization. The effective coefficients